Interactions Between Air Pollution and Obesity on Blood Pressure and Hypertension in Chinese Children. Issue 5 (September 2015) - Dong, Guang-Hui; Wang, Jing; Zeng, Xiao-Wen; Chen, Lihua; Qin, Xiao-Di; Zhou, Yang; Li, Meng; Yang, Mingan; Zhao, Yang; Ren, Wan-Hui; Hu, Qian-Sheng
<x xml:space="preserve">Abstract</x> Background: Little information exists regarding the effect of interaction of obesity and long-term air pollution exposure on children's blood pressure and hypertension in areas with high levels of air pollution. The aim of this study is to assess effect modification by obesity on the association between exposure and blood pressure in Chinese children. Methods: We studied 9, 354 Chinese children, ages 5–17 years old, from 24 elementary schools and 24 middle schools in the Seven Northeastern Cities during 2012–2013. Four-year average concentrations of particles with an aerodynamic diameter ⩽10 µm (PM10), sulfur dioxide, nitrogen dioxides, and ozone (O3) were measured at the monitoring stations in the 24 districts. We used generalized additive models and two-level logistic regression models to examine the health effects. Results: Consistent interactions were found between exposure and obesity on blood pressure and hypertension. The association between exposure and hypertension was consistently larger for overweight/obese children than for children with normal-weight, with odds ratios for hypertension ranging from 1.16 per 46.3μg/m3 for O3 (95% confidence interval [CI] = 1.12, 1.20) to 2.91 per 30.6μg/m3 for PM10 (95% CI = 2.32, 3.64), and estimated increases in mean systolic and diastolic blood pressure ranging from 0.57 mmHg (95% CI = 0.36, 0.78) and 0.63 mmHg (95% CI = 0.46, 0.81) per 46.3 μg/m3 for O3 to 4.04 mmHg (95% CI = 3.00, 5.09) and 2.02 mmHg (95% CI = 1.14, 2.89) per 23.4 μg/m3 for sulfur dioxide. Conclusions: Obesity amplifies the association of long-term air pollution exposure with blood pressure and hypertension in Chinese children.